Identification of novel alphacoronaviruses in European wildlife - Tsoleridis, Theocharis (2018)
The recent emergence of SARS and MERS and the discovery of novel coronaviruses in animals and birds suggest that the Coronavirus family encompasses more members that have not yet been identified. This study describes the design and validation of a novel pan-Coronavirus PCR and its application in virus discovery in samples obtained from 813 European rodents and shrews encompassing seven different species. Novel alphacoronaviruses were detected in the species Rattus norvegicus, Microtus agrestis, Sorex araneus and Myodes glareolus. These new viruses, together with the recently described Lucheng Rn coronavirus found in China, form a distinct rodent/shrew-specific clade within the coronavirus phylogeny and genomic analysis suggests a very ancient origin rather than the global spread of these rodent and shrew viruses. These data greatly extend the knowledge of wildlife reservoirs of alphacoronaviruses and provide important insight into their origins. In addition, further virus discovery in two vole samples, using a next-generation sequencing metagenomics approach, revealed the presence of novel viruses belonging to the poxvirus, astrovirus, rotavirus, gammaherpesvirus and influenza virus families. These studies provide important insight into the true extent of virus diversity in wildlife animals.